2006
DOI: 10.1111/j.1745-4557.2006.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF SALMONELLA TYPHIMURIUM IN OYSTERS BY PCR AND MOLECULAR HYBRIDIZATION

Abstract: Because shellfish (oysters, clams and mussels) are filter feeders, i.e., able to concentrate pathogens from the surrounding waters within their tissues, they have been widely associated with outbreaks illness. The incidence of salmonellosis caused by the consumption of raw or undercooked shellfish, is a primary concern of public health agencies. Then, in recent years, more rapid and specific methods based on the DNA sequence of salmonella genes have been developed to detect low levels of pathogens in environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our results are in agreement with Corrêa et al . () which showed that extraction of DNA from enrichment broth on food samples is more efficient than DNA extraction directly from the sample, because the enrichment broth may dilute the presence of PCR inhibitor substances. However, Nascimento and Sand (), when searching for the ETEC toxins lt and st, directly from the enrichment broths did not identify any genes.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with Corrêa et al . () which showed that extraction of DNA from enrichment broth on food samples is more efficient than DNA extraction directly from the sample, because the enrichment broth may dilute the presence of PCR inhibitor substances. However, Nascimento and Sand (), when searching for the ETEC toxins lt and st, directly from the enrichment broths did not identify any genes.…”
Section: Resultsmentioning
confidence: 99%
“…The global concern of food-borne illness, particularly from ingestion of food-borne bacteria, [1][2][3] necessitates rapid detection within food and environmental matrices. Typically, bacterial cultures, 4,5 DNA-based methods, [6][7][8][9][10] and antibody-based detection schemes 11,12 are used to isolate or identify bacteria. Cultural methodology is time-consuming; bacterial pathogens often occur in low numbers and an enrichment procedure, ranging from hours to days, may be required prior to the application of a rapid detection assay.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) has been reported as one of the most promising methods for detection of pathogens, particularly Salmonella. 6,7 However, PCR-based assays must include a means to circumvent the frequent presence of inhibitors, may detect the presence of DNA, which may not be indicative of viable bacteria, and lacks sensitivity unless bacterial numbers are sufficiently high.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of worldwide outbreaks associated with bivalve shellfish have been linked to oysters, and then to clams and mussels. Oysters, which are filter feeders, often concentrate pathogenic bacteria from marine and brackish waters (8). Rising ocean temperatures seem to contribute to observed increases in outbreaks associated with oysters (27).…”
mentioning
confidence: 99%